DIVERSITY OF PLANTS USED FOR PLAITED CRAFTS BY THE DAYAK IBAN-DÃSA IN KABUPATEN SINTANG, KALIMANTAN BARAT, INDONESIA - DEWI, ASIH PERWITA; ARIYANTI, NUNIK SRI; WALUJO, EKO BAROTO (Research Center for Biology, 2016)
DEWI, A. P., ARIYANTI N. S. & WALUJO, E. B. 2016. Diversity of plants used for plaited crafts by the Dayak Iban-DÃ©sa in Kabupaten Sintang, Kalimantan Barat. Reinwardtia 15(2): 67Â â 79. â Many plants are used for making plaited crafts such as basketry and woven mats by the Dayak Iban-DÃ©sa, a sub-tribe of the Dayak in Kalimantan Barat, Indonesia. The Dayak Iban-DÃ©sa gather the craft materials mostly from the plants in the forest. However, the habitats of these plants are being threatened by deforestation. The diversity of plants used for crafts is here documented. This study recorded the scientific names of plant species used for the craft plaiting, and observed abundance of plants used for craft. Information about the plants used were gathered using non-structural interview and focus group discussion (FGD) with the informants and participants. The abundance of plaited plants was observed in 46 plots of 10 Ã 10 m2 plots by participative ecological method. Nineteen plants species were used as plaited material, belonging to four families: Arecaceae, Poaceae, Pandanaceae and Zingiberaceae. Two species of rattan (Calamus sp. and Plectocomiopsis wrayi Becc.) have the highest Index Cultural Significance (ICS) value. Those species were considered as the most valuable plant materials because of the quality of fiber, intensity on harvesting, and the resulting quality of plaited craft products. However, the demand for high quality products is not always supported by the availability of plant materials in the forest. Therefore, the cultural significance of plants (the ICS values) and their availability should be considered when determining the conservation strategy for each of these species.